2007
DOI: 10.1108/14757700710778036
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on factors affecting the relationship between CEO stock option compensation and earnings management

Abstract: Purpose -The purpose of this paper is to examine the factors affecting the relationships between CEO stock option compensation and earnings management. Design/methodology/approach -Regression of CEO stock option compensation and other factors on measures of discretionary accruals. Findings -A positive relationship between CEO stock option compensation and discretionary accruals was found, implying that earnings management is more likely where stock options are a larger part of CEO compensation. Earnings manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 71 publications
2
55
1
6
Order By: Relevance
“…However, Meek et al, (2007) argue that earnings management may be lower in large firms because, compared to other firms they have lower information asymmetry, stronger governance structures and stronger external monitoring. Also, empirical research documents that firms with financing needs and firms approaching debt covenant default triggers have higher levels of abnormal accruals, a higher incidence of GAAP violation and a higher likelihood of committing accounting fraud (Weber, 2006).…”
Section: Control Variablesmentioning
confidence: 99%
“…However, Meek et al, (2007) argue that earnings management may be lower in large firms because, compared to other firms they have lower information asymmetry, stronger governance structures and stronger external monitoring. Also, empirical research documents that firms with financing needs and firms approaching debt covenant default triggers have higher levels of abnormal accruals, a higher incidence of GAAP violation and a higher likelihood of committing accounting fraud (Weber, 2006).…”
Section: Control Variablesmentioning
confidence: 99%
“…Indeed, some previous studies have found a positive relationship between company size and financial statement reliability (McMullen, 1996; Bédard et al, 2004). In addition, Meek et al (2007) argue that earnings management may be lower in large firms. In fact, compared to other companies, they have lower information asymmetry, stronger governance structures and stronger external monitoring.…”
Section: Control Variablesmentioning
confidence: 99%
“…Similarly, Cheng and Warfield (2005) report greater earnings management (defined as using discretionary accruals to meet or beat analyst forecast) in firms that rely more heavily on equity compensation. Furthermore, Meek et al (2007) find that the relationship between equity compensation and discretionary accruals can be moderated by firm size, growth and time period. Collectively, these studies provide evidence that equity compensation is positively associated with earnings management.…”
Section: Outside Director Compensation and Earnings Managementmentioning
confidence: 87%